AB0161 CLINICAL ASSOCIATIONS AND DIAGNOSTIC POTENTIAL OF REGULATORY-LIKE B-CELLS IN SJOGREN'S SYNDROME. (June 2019) - Barcelos, Filipe; Martins, Catarina; Geraldes, Carlos; Papoila, Ana Luísa; Cardigos, Joana; Nunes, Glória; Lopes, Teresa; Alves, Nuno; Vaz-Patto, José; Branco, Jaime; Borrego, Luís Miguel
Abstract : Background: Some B-cell subsets contribute to the regulation of immune responses, mainly through the secretion of interleukin-10, which suppresses T-helper 1 (Th 1) and Th 17 cells and induces regulatory T-cells (Tregs). The role of Bregs and Tregs in Sjögren's syndrome (pSS) pathogenesis is an active field of research. Objectives: To evaluate the distribution of regulatory and effector T and B-lymphocytes, in patients with pSS and healthy controls (HC), and the relation between regulatory-like B-cell subsets and the pSS phenotype. Methods: Fifty-seven pSS patients (2002 AECG criteria) and 24 HC were included. Circulating T and B-lymphocytes were characterized by flow cytometry and groups were compared. Significance was considered for p<0.05. Results: Compared to HC, pSS patients had lower percentages (16.9 vs 32.0%, p<0.001) and absolute numbers (28 vs 81 cells/μL, p<0.001) of Breg-enriched CD24 hi CD27 + B-cells, and a decrease in CD24 hi CD38 hi B-cells percentages (6.2 vs 7.7%, p=0.09). Lower frequencies of CD24 hi CD27 + B-cells were found in anti-SSA-positive (n=38) compared to anti-SSA-negative (n=19) patients (15.0 vs 19.6%, p=0.170), as well as lower absolute counts (26 vs 31 cells/μL; p=0.173). Anti-SSA-positive patients presented higher CD24 hi CD38 hi B-cells percentages (6.2 vs 4.2%; p=0.260) and absolute counts (10 vs 5 cells/μL; p=0.343) compared to anti-SSA-negative patients. Although CD24 hi CD27 + B-cells frequencies and absolute counts did not differ between patients with active (n=27) or inactive disease (n=30), (16.9% vs 17.0%, p=0.946; 25 vs 31 cells/μl, p=0.179), patients with higher disease activity (ESSDAI≥5) (n=9) presented lower absolute counts of CD24 hi CD27 + B-cells (18 vs 31 cells/μL, p=0.096) and lower CD24 hi CD38 hi B-cells (4 vs 10 cells/μL, p=0.075), and higher Th1/Breg CD24 hi CD27 + ratios, (16.2 vs 9.2, p=0.064). Considering all patients, a negative correlation was found between the ESSDAI score and the absolute numbers of either CD24 hi CD27 + B-cells (r= -0.277; p=0.037) and Tregs (r= -0.311; p=0.019). Correlations with ESSDAI was stronger when looking at patients with ESSDAI≥5: for the percentages of CD24 hi CD27 + B-cells, r=-0.705, p=0.023; for CD24 hi CD27 + B-cells absolute counts, r= -0.644; p=0.045; and for the absolute counts of Tregs, r= -0.862; p=0.001. Using ROC curves to discriminate pSS from HC, better AUCs were obtained for CD24 hi CD27 + Breg cells (cut-off 34 cells/μL, AUC=0.81), Tregs/CD24 hi CD27 + Breg ratio (cut-off 1.98, AUC=0.74) and Th 1/CD24 hi CD27 + Breg ratio (cut-off 12.23, AUC=0.70), corresponding to a specificity for pSS of 0.83, 0.75 and 0.70, respectively, and sensitivity of 0.75, 0.72 and 0.67, respectively. In pSS, lower CD24 hi CD27 + B-cell counts, as well as higher Tregs/CD24 hi CD27 + Breg and Th 1/CD24 hi CD27 + Breg ratios, were associated to a higher frequency of autoantibodies and higher gammaglobulin. Conclusion: Our findings demonstrated a significant decrease in the Breg-enriched CD24 hi CD27 + B-cell subset in pSS, which presented a negative correlation with the disease activity. We have demonstrated significant differences in the CD24 hi CD27 + B-cell subset and respective ratios, presenting a good discriminatory capacity compared to HC. Therefore, this subset may have diagnostic utility in pSS, as it may support the presence of immune dysregulation in suspected cases that don't fulfil the pSS classification criteria. Further studies with increased number of samples and a prospective design are needed to explore this hypothesis. Disclosure of Interests: Filipe Barcelos Consultant for: Pfizer; Ely-Lilly, Speakers bureau: Novartis, Catarina Martins: None declared, Carlos Geraldes: None declared, Ana Luísa Papoila: None declared, Joana Cardigos: None declared, Glória Nunes: None declared, Teresa Lopes: None declared, Nuno Alves: None declared, José Vaz-Patto: None declared, Jaime Branco: None declared, Luís Miguel Borrego Grant/research support from: MSD, Consultant for: MSD; Tecnifar, Paid instructor for: MSD; AstraZeneca, Speakers bureau: MSD; Tecnifar; AstraZeneca